Liquid Smoke Derived from Sago Processing Solid Waste: Organic Compound Composition and Its Application for Ironwood (Intsia bijuga) Seedlings - Herman Siruru; Wilma Nancy Imlabla; Ismail Budiman (The University of Lampung, 2026)
Liquid smoke derived from sago processing solid waste can be utilized in various applications, depending on the raw materials and pyrolysis conditions. This study aimed to identify the chemical compounds present in liquid smoke from sago processing waste and to evaluate their effects on the growth of ironwood (Intsia bijuga) seedlings. Liquid smoke was produced through a slow pyrolysis process with an average temperature increase of 1.5–1.8 °C/min. Gas chromatography–mass spectrometry (GC–MS) analysis was used to determine the chemical composition of the liquid smoke. The liquid smoke was applied to ironwood seedlings using three treatments: without liquid smoke (AC 0), a mixture of liquid smoke and water at a ratio of 1:20 (AC 1), and 1:200 (AC 2). Observations focused on seedling height, stem diameter, and number of leaves. The results showed that liquid smoke from sago processing waste contained various organic compounds, including acids, ketones, phenolics, furans, ethers, and other related compounds, with acetic acid being the dominant component. However, the application of liquid smoke did not significantly affect the growth parameters of ironwood seedlings.